Pemanfaatan Limbah Ampas Kelapa Menjadi Pupuk Organik di SMA Yadika 5 Jakarta Barat - Sitorus, Tosty Maylangi; Kaidah, Sri; Purba, Ari Pranata Primisa; Sahaq, Anang Baharuddin; Yahya, Agung Kurnia; Miftahurrahmah, Miftahurrahmah (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2025)
SMA Yadika 5 has one of the goals, namely "Providing knowledge and skills in the field of entrepreneurship and plant cultivation that are beneficial for students and the surrounding environment". In cultivating plants, supporting materials such as organic fertilizer are needed. Coconut juice is often used as a cooking ingredient in household activities, where the pulp from coconut juice that is no longer used can generally be reprocessed into organic fertilizer. Organic fertilizer can improve the chemical, physical and biological fertility of the soil, in addition to being a source of nutrients for plants. Organic fertilizer made from coconut pulp waste for plants can be one way to carry out the goals of SMA Yadika 5. In addition, it can be a solution for agriculture or plantations for housewives or family members of SMA Yadika 5 students in urban areas. Based on the analysis of the situation around us, it turns out that teenagers are interested in learning this knowledge but have not had the opportunity because there has been no training and counseling in managing waste. The target of this training in managing household organic waste from coconut pulp is male and female teenagers at SMA Yadika 5, Kembangan District, West Jakarta.